Making Brand Designs For Small Food Msme’s In Kelurahan Sei Sikambing - Ade Rahma Ayu; Adinda; Rani Anjeli; Rahma Julita; Nurul Amreni (Outline Journal of Community Development, 2023)
Micro, Small and Medium Enterprises (MSMEs) are independent businesses, with certain assets and do not include land and buildings. People's economic activities are small scale and need to be protected to prevent unhealthy competition between other businesses. This community service aims to increase the potential of food MSMEs that can be developed in the future, the main step that can be taken is by creating a business brand to make it easier for MSMEs to promote their products both offline and online and as a marker of the characteristics of the products being sold. . This activity was carried out in several stages including interviews, planning and implementation. Based on the analysis of the results of this activity, it provides benefits and makes it easier for MSMEs to create brand design in the form of stickers that will be affixed to product packaging or on online media which is expected to increase MSME business income in Kelurahan Sei Sikambing